Polskie konteksty recepcji myśli Pierre`a Bourdieu = Receptions of Pierre Bourdieu`s ideas in Polish sociology - Kuszyk-Bytniewska, Mariola (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of the paper is to present how Polish social sciences absorb philosophical and sociological ideas of Pierre Bourdieu. Moreover, it shows how influential such notions as "habitus" or "cultural capital" are in the area of social and cultural studies in Poland. The article also suggests major trends in the reception of such concepts as "critique of scholastic reason". However, being potentially applicable and adaptable, they are not yet sufficiently known by the Polish scholars.
Keywords: Bourdieu, Pierre-Félix (francuski socjolog, filozof; 1930-2002); nauki społeczne; Polska